Value management and the practice of Arabic naming in the moral formation of Ma’had Al-jāmi‘ah students - Rosyidah, Inayatur; Gufron, Gufron; Fitrotulloh, Mohamad Rofik; Maghfur, Ta’aib (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3636, 2025)
This study addresses the limited exploration of value management practices within Islamic educational institutions, particularly in the context of traditions that shape students’ character development. One such practice is the assignment of Arabic names at Ma’had al-Jāmi‘ah, which has not been widely examined beyond its symbolic role. The purpose of this research is to analyze how this naming tradition functions as a medium for instilling moral and spiritual values in students.A descriptive qualitative approach was employed, with data collected through observations, semi-structured interviews, and documentation involving institutional leaders, mentors, and students. Data were analyzed to identify patterns of value internalization associated with the meanings embedded in the names.The findings reveal that Arabic naming serves as an educational strategy that promotes spiritual awareness, disciplined conduct, and social responsibility. Value management is implemented through systematic planning, daily habituation, and continuous behavior evaluation aligned with the semantic and moral dimensions of each name. The integration of Arabic cultural symbolism with Islamic ethical principles creates a learning environment that strengthens students’ moral and spiritual integrity.These results demonstrate that culturally rooted traditions can play a significant role in shaping value-based Islamic education. The naming practice at Ma’had al-Jāmi‘ah offers a sustainable model for character formation grounded in local culture and religious identity.